River Ganga Water as Reservoir of Microbes with Antibiotic and Metal Ion Resistance Genes: High Throughput Metagenomic Approach: Analysis of Antibiotic and Metal Ion Resistance Genes in River Ganga Water (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The large-scale use of antibiotics and trace elements contributes to their progressive environmental release and eventually to the spread of bacterial antibiotic resistance genes (ARGs) and metal ion resistance genes (MRGs). A high-throughput genomic sequencing of the microbial population was conducted in water and sediments in the Ganges River harbouring resistance genes. The results showed that a large range of resistance genes with high sediment abundance are present in the river. Beta-lactam, multidrugefflux and elfamycin were the extremely dominant ARGs. In water and sediment, ARGs such as (tuf, parY, ileS, mfd) were very abundant. In water and sediments, the most abundant metal resistance gene was the MRGs subtype acn. Most of the types of ARGs showed a strong positive correlation (p ⁇ 0.05) with the types of MRGs in the river area, indicating that their distribution and transfer could be related. The taxonomic classification showed that the two most common phyla were Proteobacteria and Actinobacteria in water and sediments. The most abundant genera were Arcobacter, Terrimicrobium, Acidibacter and Pseudomonas. This study indicates that the production of resistance genes and their subsequent proliferation and accumulation in environmental bacteria is driven by antibiotics and metals. The present genomic study highlights the value of such studies and draws attention to the mitigation of contaminants associated with the distribution of ARGs and MRGs in the river setting.